2023
DOI: 10.3390/horticulturae9070743
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Population Structure Analysis of Anatolian Kara Grapevine (Vitis vinifera L.) Germplasm Using Simple Sequence Repeats

Nur Arslan,
Funda Yılmaz Baydu,
Nahid Hazrati
et al.

Abstract: Grape (Vitis vinifera L.) is among the most important commercial fruit species grown worldwide in terms of its economic value. Anatolia (Turkey), located in the favorable climate zone for viticulture, has a rich grape genetic potential due to its location at the intersection of the grapevine gene centers. In Turkish Kara grape germplasm, there are problems in terms of accuracy during the production phase due to the inadequacies in ampelographic definitions, and also very little information is available on gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…On the other hand, this study's accumulative IP reached the value of 7,5 × 10 −20 , 44.4% lower than the value obtained in the work on Andalusian varieties (1.7 × 10 −19 ) for 20 SSRs in both cases. With respect to the other works consulted [45][46][47][48][49][50][51], the values were always significantly lower (except for PI) and uneven, mainly due to the low number of samples analysed and not due to a loss of efficiency and efficacy of the SSRs used.…”
Section: Ssr Polymorphismmentioning
confidence: 64%
See 1 more Smart Citation
“…On the other hand, this study's accumulative IP reached the value of 7,5 × 10 −20 , 44.4% lower than the value obtained in the work on Andalusian varieties (1.7 × 10 −19 ) for 20 SSRs in both cases. With respect to the other works consulted [45][46][47][48][49][50][51], the values were always significantly lower (except for PI) and uneven, mainly due to the low number of samples analysed and not due to a loss of efficiency and efficacy of the SSRs used.…”
Section: Ssr Polymorphismmentioning
confidence: 64%
“…Before pointing out the statistical parameters that give confidence in the chosen SSRs, it should be borne in mind that the values found for each population depend on three conditioning factors: (a) the number of SSRs used, (b) the number of samples analysed and (c) the proximity of the population samples to be analysed, which is why it is difficult to compare with other authors [45][46][47][48][49][50][51][52]. It should be noted that the sample under study is a population belonging to an almost desert island where viticulture has been lost over the years, which is why only 40 samples have been collected.…”
Section: Ssr Polymorphismmentioning
confidence: 99%
“…Obviously, this was because it was a group of islands with different and more numerous local varieties than a single island. The several studies carried out on the mainland [48][49][50], always give higher results due to the greater diversity of their samples. On the other hand, the mean Na value was not significantly different from studies on varieties from Turkey [48] and Croatia [49], but lower than studies on the Balearic and Canary Islands [6,16].…”
Section: Ssr Polymorphismmentioning
confidence: 99%
“…The several studies carried out on the mainland [48][49][50], always give higher results due to the greater diversity of their samples. On the other hand, the mean Na value was not significantly different from studies on varieties from Turkey [48] and Croatia [49], but lower than studies on the Balearic and Canary Islands [6,16]. The mean genetic diversity index, or He, was 0.737, within the range of most of the studies consulted and slightly higher than the one found in Lanzarote, as its population was more uniform [42].…”
Section: Ssr Polymorphismmentioning
confidence: 99%